Recent advances on CAR-T signaling pave the way for prolonged persistence and new modalities in clinic - Smirnov, Sergei; Mateikovich, Polina; Samochernykh, Konstantin; Shlyakhto, Evgeny (Frontiers in Immunology, 2024)
Chimeric antigen receptor T-cell (CAR-T) therapy has revolutionized the treatment of hematological malignancies. The importance of the receptor costimulatory domain for long-term CAR-T cell engraftment and therapeutic efficacy was demonstrated with second-generation CAR-T cells. Fifth generation CAR-T cells are currently in preclinical trials. At the same time, the processes that orchestrate the activation and differentiation of CAR-T cells into a specific phenotype that predisposes them to long-term persistence are not fully understood. This review highlights ongoing research aimed at elucidating the role of CAR domains and T-cell signaling molecules involved in these processes.